The Effect of Relying on the Accuracy Of Diagnostic Tests in Medical Laboratories: A Theoretical Review from the Staff of the New Najran General Hospital Laboratory (The Review of Diabetic Studies, 2024)
The issue about the reliability of in vitro diagnostic results presented in medical laboratories has continued to be a concern for all nations concerned about the quality of healthcare. Thousands of patients are victims of false diagnoses as a result of errors on the part of medical laboratories. This accreditation is unique, conforming to national and international standards. Studies show standardization reduces errors and improves reliability. However, there is limited research on the economic effects, especially in Ethiopia. This study examines the impact of accreditation on medical laboratories using parametric and non-parametric approaches. The results indicate that implementing accreditation programs significantly improves the reliability of diagnostic tests. Policy should prioritize promoting accreditation for more reliable results.